2018
DOI: 10.1002/jbmr.3652
|View full text |Cite
|
Sign up to set email alerts
|

Dual Targeting of Bile Acid Receptor-1 (TGR5) and Farnesoid X Receptor (FXR) Prevents Estrogen-Dependent Bone Loss in Mice

Abstract: Osteoporosis is a global bone disease characterized by reduced bone mineral density (BMD) and increased risk of fractures. The risk of developing osteoporosis increases with aging, especially after menopause in women. Discovering the signaling pathways that play a significant role in aging‐ and menopause‐induced osteoporosis should accelerate osteoporosis drug discovery. In this study, we found that bile acid membrane receptor Tgr5 knockout C57BL/6J mice had similar bone mass as wild‐type mice during early and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 37 publications
3
41
0
Order By: Relevance
“…Recent research has shown that osteoporosis is commonly seen among patients with chronic cholestasis (Guañabens and Pareś, 2018), and TGR5 knockout strongly induced osteoclast differentiation in an OP mouse model (Li et al, 2019). Bile acids can also regulate bone turnover, but the functions of specific bile acids are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that osteoporosis is commonly seen among patients with chronic cholestasis (Guañabens and Pareś, 2018), and TGR5 knockout strongly induced osteoclast differentiation in an OP mouse model (Li et al, 2019). Bile acids can also regulate bone turnover, but the functions of specific bile acids are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acid receptors are expressed in many cells implicated in innate immunity, are present in the myeloid lineage, and may impact expansion of these cells ( 8 ). Bone marrow also has the ability to recognize bile acids ( 9 , 10 ). Epigenetic effects may result from signaling via bile acids, including inducing methyltransferase activity ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although many efforts have been made to develop selective FXR or TGR agonists with reduced side effects, research shows that dual agonism of FXR and TGR5 is extremely useful in the treatment of diabetes mellitus, obesity [76], NASH [55,77], atherosclerosis [78], and even other diseases like bone loss [79]. These results demonstrate the potential of FXR/TGR5 dual-targeting agonists as a promising therapy.…”
Section: Fxr and Tgr5 Dual Targeting Agonists And Other Dual Targetinmentioning
confidence: 99%
“…As mentioned before, active triterpene, like Hedragonic acid and BTA, are another kind of molecules being able to activate FXR and TGR5, so it is possible that FXR/TGR5 dual-targeting agonists can be triterpene. Li et al screened 35 BTA derivatives using TGR5-dependent cAMP accumulation and FXR response element reporter gene expression [79]. They found that SH-479, which was first synthesized by Xu et al [82], was a potent TGR5 and FXR dual agonist (Fig.…”
Section: Fxr and Tgr5 Dual Targeting Agonists And Other Dual Targetinmentioning
confidence: 99%